An interferon gamma release assay specific for Histoplasma capsulatum to detect asymptomatic infected individuals: A proof of concept study (2018)
ABSTRACT : Histoplasmosis is the most common endemic mycosis in the Americas. Currently, there is no laboratory test capable to detect subclinical or latent infections by Histoplasma capsulatum (Hc), which might develop as severe infections in immunocompromised individuals. For the first time to our knowledge, we explore the suitability of an interferon gamma release assay (IGRA) to detect latent Hc infection in asymptomatic individuals. A cohort of 126 volunteers was enrolled in the study, 13 of which underwent a Hc infection in the past, and 93 of them showing risk factors for this infection. The remaining 20 participants did not refer any risk factors of Hc infection, but eight of them showed evidences of infection with Mycobacterium tuberculosis. All participants were recruited in Medellin, Colombia, between January 2014 and December 2017. Whole blood samples were cultured with four different Hc crude antigens and phytohemaglutinin as positive control. The interferon (IFN)-γ released by T lymphocytes upon antigen stimulation was quantified by ELISA. A defined cutoff value of 20 pg/ml for the IFN-γ concentration allowed us to distinguish between the group with documented past infections and the group of noninfected individuals with high sensitivity (70– 92%) and specificity (85–95%), for the four tested antigens. Positive 82–95% and negative 77–92% predictive values were also very high, comparable to those reported for commercially available IGRAs. The new test constitutes a promising screening method to detect individuals with latent Hc infection, even decades after the primary infection, as evidenced in this study.